DETERMINAN PERTUMBUHAN LABA PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Suroso, Serli Safitri; Afrah Junita; Mayang Murni (Jurnal Mahasiswa Akuntansi Samudra, 2025)
This study aims to analyze the effect of credit interest rates, productive asset quality, and non-performing loans on profit growth of banking companies listed on the Indonesia Stock Exchange (IDX) in the period 2019-2023. The sampling technique in this study used purposive sampling taken according to the criteria used in purposive sampling registered during the research year of 7 companies. The data collection method comes from the history of banking company financial reports for the period 2014-2023, and the data analysis method used in this study is multiple linear regression using SPSS tools. The results of the study indicate that credit interest rates have a negative and significant effect on profit growth. Meanwhile, the quality of productive assets has a significant positive effect on profit growth and non-performing loans have a positive but insignificant effect on profit growth. The limitations of this study are the time period studied, which affects the relevance of the research findings. So it can be suggested to conduct a comparative study or reduce the research period.